The Involutional Change of the Anterior Segment Morphology, Intraocular Pressure and Ocular Pulse Amplitude and the Effect of Glaucoma on This Change - Comert, Ebru; Beden, Umit; Kuruoglu, Seda; Sonmez, Baris; Ozarslan, Mehtap; Yeter, Volkan; Oge, Ihsan (Turkish Ophthalmological Soc, 2013)
Purpose: To assess the involutional change of the anterior segment morphology, intraocular pressure, ocular pulse amplitude and the effect of glaucoma on these parameters. Material and Method: Fifty-five old patients with primary open-angle glaucoma (POAG) (group 1), 51 old (group 2) and 84 young individuals (group 3) without glaucoma were included in the study. We measured anterior chamber depth (ACD),anterior chamber volume (ACV), and central corneal thickness (CCT) by Scheimpflug anterior segment analyzer. Intraocular pressure (IOP) and ocular pulse amplitude (OPA) were measured by dynamic contour tonometer. Intergroup comparisons were performed for each parameter. Results: ACD in groups 1, 2, and 3 was 2.77, 2.95, and 3.37, respectively, and was different between young and old individuals demonstrating a decrease with increasing age (p: 0). ACV in groups 1,2, and 3 was 85.05, 89.6, and 127.2 mm3, respectively, being different between young and old individuals and decreased with increasing age ( p: 0). CCT in groups 1, 2, and 3 was 539.2, 539.5, and 556.7 mu m, respectively, and was different between young and old individuals showing a decrease with increasing age. IOP (16.4, 15.4, and 14,8 mmHg in groups 1, 2, and 3, respectively) was insignificantly higher in old patients without glaucoma than in young individuals. OPA (2.5+0.8 mmHg, 2.3+0.7 mmHg, and 1.9+0.8 mmHg in groups 1, 2, and 3, respectively) increased with age, and the difference was significant between young and old individuals. The diagnosis of POAG did not result in a significant difference between old patients for all parameters. Discussion: Anterior segment morphology, IOP and OPA change with age, while POAG does not affect the involutional changes in these parameters.
Keywords: Intraocular Pressure; Involutional Change; Ocular Pulse Amplitude; Anterior Segment Morphology; Primary Open-Angle Glaucoma